Book point / Siti Nurhanim Mohd Noh ... [et al.] - Mohd Noh, Siti Nurhanim; Ghazali, Nor Syahira; Sulaiman, Nur A’isyah; Abdullah, Nurani (Universiti Teknologi MARA, Kedah, 2019)
The Book Point is an application for encouraging library user to read books from library. This application is designed to promote the culture of reading for all age group from kids, teenagers, adult and etc. Lack of reading is one of common problems that always occured. Hence, with this application will be able to attract people’s attention to instill the culture of reading by providing multiple features to be applied in the Book Point application. This application is come out with a QR Code that will be placed on selected book and user need to scan the QR Code and the data will be in the user’s account. By using Book Point, user will earn some rewards for their reading activities only if they answered a few questions provided in the application.